Multitarget-Directed Ligands Combining Cholinesterase and Monoamine Oxidase Inhibition with Histamine H3 R Antagonism for Neurodegenerative Diseases - Bautista-Aguilera, Óscar M; Hagenow, Stefanie; Palomino-Antolin, Alejandra; Farré-Alins, Víctor; Ismaili, Lhassane; Joffrin, Pierre-Louis; Jimeno, María L; Soukup, Ondřej; Janočková, Jana; Kalinowsky, Lena; Proschak, Ewgenij; Iriepa, Isabel; et al. (Angewandte Chemie (International ed. in English), 2017)
The therapy of complex neurodegenerative diseases requires the development of multitarget-directed drugs (MTDs). Novel indole derivatives with inhibitory activity towards acetyl/butyrylcholinesterases and monoamine oxidases A/B as well as the histamine H3 receptor (H3R) were obtained by optimization of the neuroprotectant ASS234 by incorporating generally accepted H3R pharmacophore motifs. These small-molecule hits demonstrated balanced activities at the targets, mostly in the nanomolar concentration range. Additional in vitro studies showed antioxidative neuroprotective effects as well as the ability to penetrate the blood-brain barrier. With this promising in vitro profile, contilisant (at 1 mg kg-1 i.p.) also significantly improved lipopolysaccharide-induced cognitive deficits.
Keywords: antagonisté histaminového receptoru H3; Blood-Brain Barrier; Cholinesterase Inhibitors; antioxidancia; Histamine H3 Antagonists; Piperidines; neuroprotektivní látky; ligandy; indoly; Monoamine Oxidase Inhibitors; Neurodegenerative Diseases; kognitivní dysfunkce; racionální návrh léčiv; Ligands; Neuroprotective Agents; inhibitory MAO; Cognitive Dysfunction; piperidiny; drug design; neurodegenerativní nemoci; Animals; lidé; Antioxidants; inhibitors; Humans; Indoles; zvířata; multitarget drugs; myši; Drug Design; Mice; cholinesterasové inhibitory; antioxidants; neurological agents; hematoencefalická bariéra